The Martini 3 lipidome: expanded and refined parameters improve lipid phase behavior - Pedersen, Kasper; Ingólfsson, Helgi I.; Ramirez-Echemendia, Daniel P.; Borges-Araújo, Luís; Andreasen, Mikkel D.; Empereur-mot, Charly; Melcr, Josef; Ozturk, Tugba N.; Bennett, W. F. Drew; Kjølbye, Lisbeth R.; Brasnett, Christopher; Corradi, Valentina; et al. (ACS central science, 2025)
Lipid membranes are central to cellular life. Complementing experiments, computational modeling has been essential in unraveling complex lipid-biomolecule interactions, crucial in both academia and industry. The Martini model, a coarse-grained force field for efficient molecular dynamics simulations, is widely used to study membrane phenomena but has faced limitations, particularly in capturing realistic lipid phase behavior. Here, we present refined Martini 3 lipid models with a mapping scheme that distinguishes lipid tails that differ by just two carbon atoms, enhancing the structural resolution and thermodynamic accuracy of model membrane systems including ternary mixtures. The expanded Martini lipid library includes thousands of models, enabling simulations of complex and biologically relevant systems. These advancements establish Martini as a robust platform for lipid-based simulations across diverse fields.